2018
DOI: 10.1186/s12955-018-0849-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 24-item recovery assessment scale-revised (RAS-R) in the Norwegian language and context: a multi-centre study

Abstract: BackgroundThe Recovery Assessment Scale-revised (RAS-R) is a self-report instrument measuring mental health recovery. The purpose of the present study was to translate and adapt the RAS-R into the Norwegian language and to investigate its psychometric properties in terms of factor structure, convergent and discriminant validity and reliability in the Norwegian context.MethodsThe present study is a cross-sectional multi-centre study. After a pilot test, the Norwegian version of the RAS-R was distributed to 231 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
2
16
0
1
Order By: Relevance
“…The sample reported relatively high scores for the recovery domains pertaining to goal and success orientation and willingness to ask for help, compared to the lower Measures of personal and clinical recovery are not highly correlated (Andresen, Caputi and Oades, 2010), which might be a function of the distinction between personal and clinical recovery (Rowe and Davidson, 2016). The results for recovery in the current study were comparable to the results of a cross-sectional study with persons with mental health problems in specialist or community care (Biringer and Tjoflåt, 2018).…”
Section: Reported Levels Of Recovery and Quality Of Lifesupporting
confidence: 79%
See 2 more Smart Citations
“…The sample reported relatively high scores for the recovery domains pertaining to goal and success orientation and willingness to ask for help, compared to the lower Measures of personal and clinical recovery are not highly correlated (Andresen, Caputi and Oades, 2010), which might be a function of the distinction between personal and clinical recovery (Rowe and Davidson, 2016). The results for recovery in the current study were comparable to the results of a cross-sectional study with persons with mental health problems in specialist or community care (Biringer and Tjoflåt, 2018).…”
Section: Reported Levels Of Recovery and Quality Of Lifesupporting
confidence: 79%
“…Recovery was measured with the Norwegian version (Biringer and Tjoflåt, 2018) of the Recovery Assessment Scale -Revised (RAS-R) (Giffort et al, 1995).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cronbach’s alpha coefficients for the total scale and two subscales exceeded 0.85, indicating high internal consistency reliability of the RAS-8. This finding is comparable to previous observations showing Cronbach’s alphas greater than 0.70 for the full RAS scale in both Chinese and non-Chinese samples [ 19 21 , 24 ]. Although Cronbach’s alpha coefficients are sensitive to the number of items and decrease with reduced items [ 59 ], the relatively higher Cronbach’s alpha coefficients of the shorter version of RAS than the full version further demonstrates item homogeneity and internal consistency of the RAS-8.…”
Section: Discussionsupporting
confidence: 90%
“…Although the 24-item RAS has been the most widely-used and well-validated tool for recovery measurement, a review showed that other item numbers have also been used including 20, 22, 24, 41, 42 and 50 [ 9 ]. Another cross-sectional multi-center validation study of the 24-item RAS conducted in a Norwegian context found some item redundancy among the factors (such as Personal confidence and hope, Goal and success orientation and Not dominated by symptoms) [ 24 ]. This finding is further echoed in a recent study examining the factor structure of the 24-item RAS in a German sample, which supported a 14-item RAS by confirmatory factor analysis [ 23 ].…”
Section: Introductionmentioning
confidence: 99%